Stationary QH-mode plasmas with high and wide pedestal at low rotation on DIII-D. (30th September 2016) - Chen, Xi; Burrell, K.H.; Osborne, T.H.; Solomon, W.M.; Barada, K.; Garofalo, A.M.; Groebner, R.J.; Luhmann, N.C.; McKee, G.R.; Muscatello, C.M.; Ono, M.; Petty, C.C.; et al.
Abstract: A stationary, quiescent H-mode (QH-mode) regime with a wide pedestal and improved confinement at low rotation has been discovered on DIII-D with reactor relevant edge parameters and no ELMs. As the injected neutral beam torque is ramped down and the edge E   ×   B rotation shear reduces, the transition from standard QH to the wide pedestal QH-mode occurs. At the transition, the coherent edge harmonic oscillations (EHO) that usually regulate the standard QH edge cease and broadband edge MHD modes appear along with a rapid increase in the pedestal pressure height (by  ⩽60%) and width (by  ⩽50%). We posit that the enhanced edge turbulence-driven transport, enabled by the lower edge E   ×   B flow shear due to lower torque reduces the pedestal gradient and, combined with the high edge instability limit provided by the balanced double-null plasma shape, permits the development of a broader and thus higher pedestal that is turbulence-transport-limited. Even with the significantly enhanced pedestal pressure, the edge operating point is below the peeling ballooning mode stability boundary and thus without ELMs. Improved transport in the outer core region (0.8  ⩽   ρ   ⩽0.9) owing to increased E   ×   B flow shear in that region and the enhanced pedestal boost the overall confinement by up to 45%. These findings advance the physics basis for developing stationary ELM-free high-confinement operation at low rotation for future burning plasma where similar collisionality and rotation levels are expected.